The comparison of the risk of neurological deterioration and clinical outcomes in different atherosclerotic stroke patterns - Yue He; Tingting Zhang; Wenqi Wu; Kai Niu; Zhirong Cai; Tian Zhao; Yuanwei Shao; Yi Yang; Ying Zhu; Ming Yu (Scientific Reports)
Abstract This study aims to compare the incidences of neurological deterioration (ND) and poor outcome (a modified Ranking scale > 2 points at discharge) among patients with different atherosclerotic stroke patterns. A total of 688 participants were categorized into 4 groups according to atherosclerotic stroke pattern: multiple small infarcts (MSI), single subcortical infarction (SSI), borderzone infarct (BZI) and large infarct groups. Among the 4 groups, MSI group had the lowest incidences of ND and poor outcome (13.5% and 16.2%, respectively). In multivariable analyses, for BZI patients, the risks of ND [odds ratio (OR) = 3.90, 95% confidence interval (CI) = 2.10–7.22, p < 0.001] and poor outcome (OR = 3.45, 95% CI = 1.67–7.14, p = 0.001) both significantly increased compared to MSI, both of which were the highest among the 4 stroke patterns. The neutrophil to lymphocyte ratio in BZI and large infarct groups were higher than in MSI and SSI groups [3.35 (2.28, 5.04) and 3.36 (2.53, 4.94) vs. 2.64 (1.89, 4.06) and 2.71 (1.93, 3.91), p < 0.001]. BZI group had the highest risks of ND and poor outcome among atherosclerotic stroke patients. BZI and large infarct patients had stronger poststroke inflammation than MSI and SSI patients.